Platelets and Megakaryocytes in Vascular Disease - van der Loo, B.; Martin, J. F. (Hämostaseologie, 1996)
Platelets are involved in both atherosclerosis and its complications including coronary artery thrombosis. They are derived from their precursor, the mega-karyocyte (MK), a unique cell in mammalians as it can double its DNA content without intervening mitoses. There is growing evidence that changes in the megakaryocyte - platelet - haemostasis axis precede acute thrombotic events, therefore suggesting a preexisting prethrombotic state prior to thrombosis. In this context, interest has focused on changes in megakaryocyte DNA content and its relationship to platelet reactivity. An increase in MK ploidy may be associated with the production of large platelets. Large platelets are denser and are more reactive haemostatically. Mean platelet volume (MPV) is increased in patients immediately after myocardial infarction (Ml) and is a predictor of a further ischaemic event when measured after Ml.One of the haematopoietic factors that regulate megakaryocytopoiesis has recently been characterized as the c-mpl ligand. This finding, and an understand-ing of the signalling system that controls not only platelet number but also size, might give insight into a role for platelet production in thrombogenesis and athe-rogenesis.
Keywords: Platelets; megakaryocytes; atherosclerosis; coronary heart disease (CHD)